2004
DOI: 10.1038/sj.npp.1300541
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine-Associated Cues Maintain Nicotine-Seeking Behavior in Rats Several Weeks after Nicotine Withdrawal: Reversal by the Cannabinoid (CB1) Receptor Antagonist, Rimonabant (SR141716)

Abstract: Conditioned stimuli are important for nicotine dependence and may trigger craving and relapse after prolonged nicotine abstinence. However, little is known about the pharmacology of this process. Among the systems that have been shown to play a role in drugseeking behavior is the endocannabinoid transmission. Therefore, the present study examined the resistance to extinction of drugseeking behavior elicited by nicotine-associated environmental stimuli and the effects of the selective CB 1 cannabinoid antagonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
176
2
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(203 citation statements)
references
References 49 publications
17
176
2
3
Order By: Relevance
“…In answer to this question a sizeable literature suggests that smoking is maintained by both the primary reinforcing properties of nicotine and its related ability to establish associated environmental stimuli as conditioned stimuli, which can subsequently induce craving and provoke drug-seeking (Rose and Levin 1991;Perkins 1999;Caggiula et al 2001;Cohen et al 2005). Research by our laboratory concurs fully with this hypothesis, but extends it to include a distinct behavioral property of nicotine -its capacity to enhance responding for an already reinforcing non-nicotine stimulus Chaudhri et al in press).…”
Section: Nicotine Self-administration Is Obtained Under Finite Experisupporting
confidence: 62%
“…In answer to this question a sizeable literature suggests that smoking is maintained by both the primary reinforcing properties of nicotine and its related ability to establish associated environmental stimuli as conditioned stimuli, which can subsequently induce craving and provoke drug-seeking (Rose and Levin 1991;Perkins 1999;Caggiula et al 2001;Cohen et al 2005). Research by our laboratory concurs fully with this hypothesis, but extends it to include a distinct behavioral property of nicotine -its capacity to enhance responding for an already reinforcing non-nicotine stimulus Chaudhri et al in press).…”
Section: Nicotine Self-administration Is Obtained Under Finite Experisupporting
confidence: 62%
“…Previous studies have also reported that rimonabant blocks the reinforcing effects of nicotine (Cohen et al, 2002) and avoids reinstatement of nicotine seeking in rats (Cohen et al, 2005).…”
Section: Previous Studies Have Reported Behavioural Interactions Betwmentioning
confidence: 90%
“…Briefly, rimonabant has been found to decrease nicotine self-administration (Cohen et al 2002;Kodas et al 2007), cue-induced reinstatement of nicotine seeking (Cohen et al 2004;De Vries et al 2005), and nicotine-conditioned place preferences (Forget et al 2005;Le Foll and Goldberg 2004). The operant discriminative stimulus (S D ) effects of nicotine do not appear to be affected by pretreatment with rimonabant (Cohen et al 2002;Le Foll and Goldberg 2004;Zaniewska et al 2006).…”
Section: Introductionmentioning
confidence: 99%